Line Balancing Analysis Using Ranked Positional Weight and Region Approach Methods on Broad Plate Production Line - Rizki Rahmantto, Muhammad; Widjajati, Endang Pudji (Newinera Publisher, 2025)
PT. Risa Implantama is a company engaged in the production of bone implants that focuses on the production of bone pins and screws. This company produces bone pins with various types and then markets the production results through distributors and also produces goods according to incoming orders, both from distributors and hospitals. Rapid advances in medical science and technology have significantly improved the quality and longevity of human life. The field of orthopedics in the world of medicine has also experienced technological advances in dealing with various cases in its field, one of which is bone fractures. Based on initial calculations, the line efficiency was 51.07%, then the balance delay was 48.93% and the idle time was 1.90 minutes. After processing the data using the ranked positional weight method for the line efficiency of the broad plate production process, the line efficiency results were 64.42%, then the balance delay was 35.58% and the idle time was 14.64 minutes. Furthermore, after data processing using the region approach method for the line efficiency of the broad plate production process, the line efficiency results were 54.47%, then for the balance delay of 45.53% and idle time of 14.64 minutes. Based on the calculation results, the Ranked Positional Weight (RPW) method is the optimal method in solving line balancing, because it has the highest Line Efficiency (LE) value and the lowest Balance Delay (BD).